Missions and empire - Etherington, Norman (Oxford ; New York : Oxford University Press, 2005)
The widespread idea that Christian missions went hand in hand with Imperialism and colonial conquest is challenged here by a group of eminent historians. By showing the variety of missions and the vital role played by indigenous men and women, they place missions in a long historical perspective. Special attention is paid to emerging themes such as the missionary role in anthropology, gender relations, language, medicine, and decolonization. The explosive expansion of Christianity in Africa and Asia during the last two centuries constitutes one of the most remarkable cultural transformations in the history of mankind. Because it coincided with the spread of European economic and political hegemony, it tends to be taken for granted that Christian missions went hand in hand with Imperialism and colonial conquest. In this book historians survey the relationship between Christian missions and the British Empire from theseventeenth century to the 1960s and treat the subject thematically, rather than regionally or chronologically. Many of these themes are treated at length for the first time, relating the work of missions to language, medicine, anthropology, and decolonization. Other important chapters focus on thedifficult relationship between missionaries and white settlers, women and mission, and the neglected role of the indigenous evangelists who did far more than European or North American missionaries to spread the Christian religion - belying the image of Christianity as the 'white man's religion'.
"A marvellous resource for teaching ... an excellent introduction"--Elizabeth Elbourne, Journal of Southern African Studies; "a wonderful addition to the OHBE series"--ten Walles, British Scholar; "offers a multifaceted and thought-provoking study of the relationship between missions and the British Empire"--Kevin Grant, Journal of British Studies; "This book features essays of uniformly high quality that articulate many important parts of the relationship between missions and empire"--Kevin Grant, Journal of British Studies; "wide-ranging and well-written collection"--James Munson, Contemporary Review; "The history of missions recounted in these fascinating essays underscores the importance of the social relations of lived religion, of privileges defended and feet left unwashed"--Susan Thorne, History Workshop Journal; "There is much to admire, and the book ought to continue the debate on the relationship between British mission societies and the Empire"--Helena Bethea Gardner, Journal of Pacific History; "makes the case for a fresh look at the relationship between missions and empire and from a variety of disciplinary perspectives" - David Arnold, THES; "wide-ranging and well-written collection of thirteen essays" - Contemporary Review; "important and fascinating collection of essays" - Church of England Newspaper; "the collection is a marvellous resource for teaching" - Journal of Southern African Studies.
Prelude: the Christianizing of British America / Eliga H. Gould -- An overview, 1700-1914 / Andrew Porter -- Humanitarians and white settlers in the nineteenth century / Alan Lester -- Where the missionary frontier ran ahead of empire / John Barker -- Christian missions and the Raj / Robert Eric Frykenberg -- New Christians as evangelists / Peggy Brock -- 'Trained to tell the truth': missionaries, converts, and narration / Gareth Griffiths -- Women and cultural exchanges / Patricia Grimshaw and Peter Sherlock -- Language / Paul Landau -- New religious movements / Rober Edgar -- Anthropology / Patrick Harries -- Education and medicine / Norman Etherington -- Decolonization / David Maxwell.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Missions, British -- History; Christianity and politics -- Great Britain -- Colonies -- History; Imperialism -- History; Great Britain -- Colonies -- Religion; Missions britanniques -- Histoire; Christianisme et politique -- Grande-Bretagne -- Colonies -- Histoire; Impérialisme -- Histoire; Grande-Bretagne -- Colonies -- Religion; RELIGION -- Christian Ministry -- Missions; British colonies; Imperialism; Missions, British; Religion; Great Britain; Imperialisme; Zending; Electronic books; History